Effects of radiation doses from different dental imaging modalities on cell-implant interaction: A comparison with cell culture study - Mehmet Hakan Kurt; Bengi Oztas; Arzu Atalay (Wolters Kluwer Medknow Publications, 2016)
Objectives: The effect of radiation after exposing with dental imaging devices on cell-implant material interaction has not been adequately studied. The aim of this study is to determine the effects of radiation by measuring proliferation and differentiation of the human fetal osteoblast (hFOB) cells using dental imaging techniques and evaluate the result in vitro conditions at cellular stage. Materials and Methods: hFOB were irradiated 1 day after planting on commercially pure titanium discs. Radiation was single dose in one exposure using five different dental imaging techniques as conventional dental and digital dental X-ray tubes, conventional panoramic, digital panoramic and cone beam computerized tomography (CBCT). In the 8 th day of experiment, exposured cells and nonexposured control group cells which planted on discs were compared and examined regarding their proliferations and alkaline phosphatase (ALP) activities. Results were evaluated using Student's Independent t-test in SPSS 15.0 (SPSS Inc., Chicago, IL, USA). Results: In exposure with digital dental imaging device, ALP activities of cells are increased according to the control group and statistically, with 0, 2 s of exposure, a significant increment was found (P < 0.05). The exposures with CBCT and conventional dental imaging devices decreased cell proliferation compared with the control groups, but it was found statistically insignificant. In exposure with the other dental imaging devices, cell proliferation increased insignificantly. Conclusions: Our in vitro study suggests that the ionizing radiation produced by digital dental imaging devices may result to certain increment of the cell number and activities. More controlled study should be made with cell cultures in order to verify the exact activity of digital dental imaging.